2020
DOI: 10.1088/1475-7516/2020/03/032
|View full text |Cite
|
Sign up to set email alerts
|

It is feasible to directly measure black hole masses in the first galaxies

Abstract: In the local universe, black hole masses have been inferred from the observed increase in the velocities of stars at the centres of their host galaxies. So far, masses of supermassive black holes in the early universe have only been inferred indirectly, using relationships calibrated to their locally observed counterparts. Here, we use the latest observational constraints on the evolution of stellar masses in galaxies to predict, for the first time, that the region of influence of a central supermassive black … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Specifically, since the stellar mass evolves much more modestly than the black hole mass (also found in recent observations, e.g., [195,196]), the dominance of the black hole can be felt at high redshifts to a much greater distance from the centre of the system. This leads to a direct, observable signature [197] of the prevalence of massive black holes in the centres of the first galaxies during the period of reionization. It is found that the influence of the central black hole can dominate the kinematics up to a distance of 0.5 kpc from the centre of the dark matter halo at redshifts z 6.…”
Section: Multi-messenger Cosmology: the Gravitational Wave Regimementioning
confidence: 99%
“…Specifically, since the stellar mass evolves much more modestly than the black hole mass (also found in recent observations, e.g., [195,196]), the dominance of the black hole can be felt at high redshifts to a much greater distance from the centre of the system. This leads to a direct, observable signature [197] of the prevalence of massive black holes in the centres of the first galaxies during the period of reionization. It is found that the influence of the central black hole can dominate the kinematics up to a distance of 0.5 kpc from the centre of the dark matter halo at redshifts z 6.…”
Section: Multi-messenger Cosmology: the Gravitational Wave Regimementioning
confidence: 99%